Dualism in China’s Strategic Culture Implementation Through ‘Confucian-Pacifism’ and ‘Cultural Realism’ in Tackling Border Problems - Aldora, Cecilia (JUSS (Jurnal Sosial Soedirman), 2024)
This paper explores the dualism in China's Strategic Culture based on its responses to territorial disputes with countries like Japan, India, and Taiwan. Unlike just one strategic culture for a state, this research demonstrates that China simultaneously enacts two distinct, almost contradicting in a way of strategic cultures: Confucian Pacifism and Cultural Realism. Whereas Confucian Pacifism is dialogical and harmony-oriented, Cultural Realism carries the act of pragmatism entailing threats or use of force. Dualism created by these two strategic cultures is what one needs to recognize in order to really appreciate the multi-dimensional with which China has treated international relations and border conflict. This paper discusses how these two strategic cultures interact and influence decision-making in influencing China's behavior on the global stage, especially in response to territorial disputes with its neighboring countries.